Coping with stress: A study of retail banking service workers in Russia. (March 2015) - Ashill, Nicholas J.; Rod, Michel; Gibbs, Tanya
Abstract: This study extends previous research on the antecedents and outcomes of frontline employee (FLE) burnout by empirically testing the direct and moderating effects of two coping strategies in a job demand stress–strain (burnout)–job performance model using data from a large Russian retail bank. Contrary to findings from North American-Western research and more limited studies of countries where collectivist values are emphasized, the study findings show that emotional exhaustion plays no mediating role in the job demand stressors–job performance relationship. Self-directed coping buffers the dysfunctional effects of job demand stressors on emotional exhaustion whereas 'other-directed' coping buffers the job demand stressors to job performance relationship. Implications of the results are discussed and future research avenues are offered. Highlights: We extend research on antecedents and outcomes of burnout to a country where collectivist values are emphasized. We examine relationships between hindrance stressors, emotional exhaustion and job performance in a large Russian retail bank. Emotional exhaustion plays no mediating role in the hindrance stressors–job performance relationship. Self-directed coping buffers the dysfunctional effects of job demand stressors on emotional exhaustion. 'Other-directed' coping buffers the job demand stressors to job performance relationship.